Legal Protection Of Victims In The Crime Of Rapes - Evi Yulianti; Achmad Sulchan (Universitas Islam Sultan Agung, 2021)
The purpose of this study is to identify and analyze the legal protection of victims in the crime of rape, and to identify and analyze the obstacles and solutions to the legal protection of victims in the crime of rape. This study uses a normative juridical approach, which in this case relates to the legal protection of victims in the crime of rape with descriptive analytical research specifications. The data used are primary and secondary data which will be analyzed qualitatively. The research problems were analyzed using law enforcement theory, legal certainty and Islamic justice theory. The results of the study concluded that the protection of victims of the crime of rape in addition to experiencing physical suffering also experienced psychological suffering which took a long time to recover. Considering that the suffering experienced by the victims of the crime of rape is not light and it takes a long time to recover, the law enforcement officers are obliged to provide protection for the victims of the crime of rape. The obstacles that arise in the legal protection of the rights of victims in the process of resolving criminal cases: a) The criminals themselves, where the perpetrators of the crime are very good at committing crimes so that they are not caught or not caught; b) The attitude of the community, where the attitude of the community is indifferent in dealing with crimes that occur in their environment, so that people are less sensitive in dealing with crimes that occur; c) The compensation given by the perpetrator to the victim is not in accordance with what the victim expects because of the economic limitations of the perpetrator of the crime; d) For immaterial losses in criminal cases it cannot be done. The solution to the legal protection of victims in the crime of rape is the rehabilitation of victims of the crime of rape.